Fabrication of GaAs devices - Baca, A. G. (Institution of Electrical Engineers, 2005)
This book provides fundamental and practical information on all aspects of GaAs processing. The book also gives pragmatic advice on cleaning and passivation, wet and dry etching and photolithography, and dry etching. Other topics covered include device performance for HBTs (Heterojunction Bipolar Transistors) and FETs (Field Effect Transistors), how these relate to processing choices, and special processing issues such as wet oxidation, which are especially important in optoelectronic devices.
Keywords: Gallium arsenide semiconductors.; elektronické knihy; electronic books